Quenched Zwitterionic Cyclic Arg-Gly-Asp-Containing Pentapeptide Probe for Real-Time Brain Tumor Imaging - Hyunjin Kim; Maixian Liu; Yongdoo Choi (MDPI AG, 2024)
The efficacy of glioblastoma treatment is closely associated with complete tumor resection. However, conventional surgical techniques often result in incomplete removal, leading to poor prognosis. A major challenge is the accurate delineation of tumor margins from healthy tissues. Imaging-guided surgery, particularly using fluorescent probes, is a promising solution for intraoperative guidance. The recently developed 'always-on' types of targeted fluorescence probes generate signals irrespective of their presence in tumor cells or in blood circulation, hampering their effectiveness. Here, we propose a novel activatable fluorescence imaging probe, Q-cRGD, that targets glioma cells via the specific binding of the cyclic Arg-Gly Asp-containing pentapeptide (cRGD) to integrins. The Q-cRGD probe was synthesized by conjugating a near-infrared (NIR) dye to a tryptophan quencher via a disulfide linkage, including a cRGD-targeting ligand. This activatable probe remained inactive until the redox-responsive cleavage of the disulfide linkage occurred within the target cell. The zwitterionic nature of NIR dyes minimizes nonspecific interactions with serum proteins, thereby enhancing the tumor-to-background signal ratio (TBR). An in vivo fluorescence imaging study demonstrated a TBR value of 2.65 within 3 h of the intravenous injection of Q-cRGD, confirming its potential utility in imaging-guided brain cancer surgery.